South Asians and the dowry problem - Menski, Werner; International Conference on Dowry and Bride-Burning. (New Delhi : Vistaar Publications, 1998)
Collection of the main papers from three International Conferences on Dowry and Bride-Burning; the 1st and 2nd conferences were held at Harvard University in 1995 and 1996 and the 3rd at London University in 1997.
Keywords: Dowry -- South Asia -- Congresses; Murder -- South Asia -- Congresses; Uxoricide -- South Asia -- Congresses; Wives -- Crimes against -- South Asia -- Congresses